Using Excel 3 for Windows - Person, Ron (Que, 1991)
This book contains six parts: *) Part I shows you how to install and run Excel. *) Part II shows you how to create, edit, format, and print worksheets. *) Part III shows you how to create, format, and manipulate charts. *) Part IV shows you how to create and maintain a database. *) Part V shows you how to record simple macros and modify them so that they request data and check it, it also explains how to build custom menus and dialog boxes and how to do more advanced programming. *) Part VI shows you how to use Excel with other software, both DOS applications - such as Lotus 1-2-3 and WordPerfect - and Windows applications - such as Word for Windows and CorelDRAW!, it also describes how to customize many of the features in Excel and Windows